Animal heroes : the wolves, camels, elephants, dogs, cats, horses, penguins, dolphins, and other remarkable animals the proved they are man's best friend /: the wolves, camels, elephants, dogs, cats, horses, penguins, dolphins, and other remarkable animals the proved they are man's best friend. (2017) - Moberg, Julia
No abstract available